HAKIKAT PSIKOLOGI SEBAGAI LANDASAN DALAM PEMBELAJARAN PAI - Nurnaesih, Nurnaesih; Muslihah, Eneng; Kultsum, Umi (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This research aims to analyze the nature of psychology as a basis for PAI learning. In its implementation, the researcher used a qualitative method of the library study type, which used secondary data as a data source. The results of this research show that the foundation of Islamic religious education that is needed in Indonesia is psychology. Psychology can provide a reference for parents and teachers in educating children according to the child's level of psychological development. In essence, psychology as a basis for learning Islamic religious education has an important role in instilling religious awareness related to children's spiritual values to develop their potential. This psychological foundation has implications for developmental, learning, and social psychology. So that it can shape children into superior humans, with Islamic character, and who can be accepted in groups or society.